2022
DOI: 10.3389/fcimb.2022.823626
|View full text |Cite
|
Sign up to set email alerts
|

The Collateral Effects of COVID-19 Pandemic on the Status of Carbapenemase-Producing Pathogens

Abstract: The serious challenge of antimicrobial resistance continues to threaten public health and lingers in the era of the coronavirus disease 2019 (COVID-19), declared pandemic by the World Health Organization. While the pandemic has triggered the importance of infection control practices and preventive measures such as physical distancing, hand hygiene, travel reduction and quarantine, the ongoing alarm of antimicrobial resistance seems to accompany the pandemic too. Antimicrobial resistance has been fostered durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 102 publications
(116 reference statements)
2
13
0
Order By: Relevance
“…Similarly, the proportions of MDR and possible XDR strains were almost reduced by half, indicating that some isolates have regained their sensitivity or at least ceased being nonsusceptible over the course of the follow-up years. The mild increase in the levels of MDR, possible XDR, and possible PDR strains toward the end of the study period may have been affected by the COVID-19, as reported elsewhere ( 66 , 67 ), and was probably driven by high rates of antimicrobial utilization and disruption of infection control measures occurring as collateral effects of the global pandemic ( 68 ). It is worth mentioning that trends in Acinetobacter species resistance were reported to have similar declining portraits in other parts of the world.…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, the proportions of MDR and possible XDR strains were almost reduced by half, indicating that some isolates have regained their sensitivity or at least ceased being nonsusceptible over the course of the follow-up years. The mild increase in the levels of MDR, possible XDR, and possible PDR strains toward the end of the study period may have been affected by the COVID-19, as reported elsewhere ( 66 , 67 ), and was probably driven by high rates of antimicrobial utilization and disruption of infection control measures occurring as collateral effects of the global pandemic ( 68 ). It is worth mentioning that trends in Acinetobacter species resistance were reported to have similar declining portraits in other parts of the world.…”
Section: Discussionmentioning
confidence: 65%
“…No carbapenemases other than KPC were identified among carbapenem-resistant Enterobacterales isolates. While during the early stages of the COVID-19 pandemic, unremarkable increases in the incidence of infections by carbapenemase-producing Enterobacterales were observed [ 26 , 27 ], such figures significantly changed later on [ 28 ]. Tiri et al reported that the incidence of KPC-producing Klebsiella pneumoniae in COVID-19 ICU patients increased significantly from 6.7% in 2019 to 50% in 2020 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review study by Langford et al found no association between COVID-19 and changes in antimicrobial resistance of gram-positive bacteria. However, a possible increase in resistance was found in gram-negative patients, suggesting an important role due to the high use of beta-lactams and third generation cephalosporins in patients with COVID-19 [48,49]. The study by Elton and colleagues at two hospitals in Africa observed an increase in the total number of HAIs caused by multidrug-resistant bacteria in COVID-19 patients.…”
Section: Impact Of the Covid-19 Pandemic On Bacterial Resistancementioning
confidence: 99%